2021
DOI: 10.3390/s21196557
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Biodegradable Printed Capacitive Humidity Sensors

Abstract: Flexible and biodegradable sensors are advantageous for their versatility in a range of areas from smart packaging to agriculture. In this work, we characterize and compare the performance of interdigitated electrode (IDE) humidity sensors printed on different biodegradable substrates. In these IDE capacitive devices, the substrate acts as the sensing layer. The dielectric constant of the substrate increases as the material absorbs water from the atmosphere. Consequently, the capacitance across the electrodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…The sensor’s transient, capacitive, and resistive responses to step input between low (45%) and high (85%) ambient % RH values are depicted in Figure a,b. It is pertinent to mention that the response time is defined as the time required for the capacitive humidity sensor to accomplish 90% of the saturated capacitance value across the high % RH region; similarly, the recovery time is defined as the time required by capacitance of the device to alter from a local maximum to within 10% of the average minimum value across the low % RH region . From Figure a, it is observed that at constant 45% RH value, the response is quite stable up to 50 s for TPPNi-ZnO nanocomposite-based capacitive sensors but increases to its maximum with an average response time of ∼30 s when % RH changes from 45 to 85%.…”
Section: Resultsmentioning
confidence: 99%
“…The sensor’s transient, capacitive, and resistive responses to step input between low (45%) and high (85%) ambient % RH values are depicted in Figure a,b. It is pertinent to mention that the response time is defined as the time required for the capacitive humidity sensor to accomplish 90% of the saturated capacitance value across the high % RH region; similarly, the recovery time is defined as the time required by capacitance of the device to alter from a local maximum to within 10% of the average minimum value across the low % RH region . From Figure a, it is observed that at constant 45% RH value, the response is quite stable up to 50 s for TPPNi-ZnO nanocomposite-based capacitive sensors but increases to its maximum with an average response time of ∼30 s when % RH changes from 45 to 85%.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage hysteresis at different volumes of water is summarized in Table 3. The percentage value of hysteresis is calculated from Equation (8) [25].…”
Section: Adsorption-desorption Study Of Sensorsmentioning
confidence: 99%
“…Numerous sensors based on various principles and substrates are available for the detection and monitoring of humidity and moisture [9,[24][25][26][27]. These are capacitive, resistive (inductive) LC resonators or optical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Such sensors can be realized on numerous sustainable and even biodegradable substrates [10]. The relationship between humidity dependent permittivity and capacitance is commonly modeled by a second order polynomial growth, which makes this type of sensors rather sensitive in a higher humidity range [11].…”
Section: Introductionmentioning
confidence: 99%